Two Honorary Doctorate Degrees Presented at 1975 Spring Graduation 5 - Opal R. Lovett
Annual spring graduation exercises were held April 25, 1975 at Jacksonville State University in Pete Mathews Coliseum. An honorary doctorate degree was bestowed upon Tom Ventress, director of Industrial Relations for the State of Alabama. Dr. Ernest Stone (JSU president) and Joe C. McCorquodale, Jr. (speaker of the Alabama House of Representatives) stand with Ventress. (circa April 25, 1975)